COT-12 CLINICAL MANAGEMENT AND TIMING OF SURGICAL TREATMENT FOR ASYMPTOMATIC GLIOMA. (16th December 2019) - Matsuda, Ryosuke; Morimoto, Takayuki; Takeshima, Yasuhiro; Tamura, Kentaro; Yamada, Shuichi; Nishimura, Fumihiko; Nakagawa, Ichiro; Motoyama, Yasushi; Park, Young-Su; Nakamura, Mitsutoshi; Nakase, Hiroyuki
Abstract: BACKGROUND: In Japan, there are many cases where intracranial diseases are found accidentally due to the widespread use of MRI and brain check-up. Unruptured cerebral aneurysms and asymptomatic cerebral infarctions are often diagnosed, but asymptomatic glioma is rarely diagnosed. We analyzed the asymptomatic gliomas retrospectively among grade 2 or higher gliomas that had undergone diagnostic imaging or surgical treatment in our institution. MATERIAL AND METHODS: Of 166 adults with grade 2 or higher grade glioma treated in our institution between 2007 and 2018, 15 cases were asymptomatic. Twelve cases were males and 3 were females, with an average age of 55.1 years (34–79 years). There were 7 cases found in brain check-up, 6 cases in the follow-up of other intracranial diseases, and 2 cases in migraine. Twelve patients, except 3 patients, have undergone surgical treatment, and the average time from an initial imaging to surgical treatment was 51.1 weeks (2 to 329 weeks). Eight patients were treated after radiological follow-up and 4 cases are treated within 2 months after the tumor was discovered. The pathological diagnosis was grade 2: 5 cases, grade 3: 2 cases, and grade 4: 5 cases. Three patients without surgical treatment were diagnosed as grade 2 on MRI. Six patients died during follow-up. The median survival time from the first surgical treatment for grade 3 and 4 glioma was 17 months. CONCLUSION: Incidence of asymptomatic glioma is very rare. Even for asymptomatic gliomas, the prognosis is not so good due to malignant transformation and disease progression. It is important to explain the natural course of disease and treatment strategy accurately.